STRATEGI DALAM PENGEMBANGAN KARAKTER PELAJAR PANCASILA - SOLCHAN GHOZALI (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2020)
This research explains the strategy carried out by SD Al-Muqoddasah in shaping the Character of Global Diversity of students into a Pancasila Student Profile.  This study used the Descriptive Qualitative Method of phenomenology with primary data sources of Vice Principals, Arabic Language Teachers, and Students of SD Al-Muqoddasah Ponorogo and Secondary data in the form of school document archives. Data Retrieval Techniques through Observation, Interviews, and Documentation, and Data Validity Techniques using source Triangulation Techniques. The results of the research obtained  in the strategy in developing the character  of pancasila students  are carried out in the form of guidance, coaching and introduction to traditions, traditional culture and others, and fostering mutual respect or tolerance for fellow students in forming students who have the characteristics of a pancasila student profile, such as loving traditional traditions and culture, being able to respect the traditions and culture of others,  can communicate and work well together when interacting with other people from any place or circle